A photo-auxiliary approach – enabling excited state classical phototransformations with metal free visible light irradiation. Issue 10 (19th January 2017) - Iyer, Akila; Jockusch, Steffen; Sivaguru, Jayaraman
Abstract : To address the problem of using UV light to initiate traditional photoreactions, hydrazide based chromophores are evaluated as a "photo-auxiliary" with visible light using a metal free photocatalyst to afford photoproducts in high yields. Abstract : Most traditional photoreactions require UV light to yield the desired product. To address this issue, photoreaction of hydrazide based chromophores was evaluated with visible light using a metal free photocatalyst to afford photoproducts in high yields. This hydrazide functionality itself may be removed/modified after the photoreaction, highlighting its role as a "photo-auxiliary". A preliminary mechanistic model based on photophysical experiments is provided to highlight the generality of the strategy.